The purine-utilizing bacterium Clostridium acidurici 9a: a genome-guided metabolic reconsideration. - Katrin Hartwich (Public Library of Science (PLoS), 2012)
Clostridium acidurici is an anaerobic, homoacetogenic bacterium, which is able to use purines such as uric acid as sole carbon, nitrogen, and energy source. Together with the two other known purinolytic clostridia C. cylindrosporum and C. purinilyticum, C. acidurici serves as a model organism for investigation of purine fermentation. Here, we present the first complete sequence and analysis of a genome derived from a purinolytic Clostridium. The genome of C. acidurici 9a consists of one chromosome (3,105,335 bp) and one small circular plasmid (2,913 bp). The lack of candidate genes encoding glycine reductase indicates that C. acidurici 9a uses the energetically less favorable glycine-serine-pyruvate pathway for glycine degradation. In accordance with the specialized lifestyle and the corresponding narrow substrate spectrum of C. acidurici 9a, the number of genes involved in carbohydrate transport and metabolism is significantly lower than in other clostridia such as C. acetobutylicum, C. saccharolyticum, and C. beijerinckii. The only amino acid that can be degraded by C. acidurici is glycine but growth on glycine only occurs in the presence of a fermentable purine. Nevertheless, the addition of glycine resulted in increased transcription levels of genes encoding enzymes involved in the glycine-serine-pyruvate pathway such as serine hydroxymethyltransferase and acetate kinase, whereas the transcription levels of formate dehydrogenase-encoding genes decreased. Sugars could not be utilized by C. acidurici but the full genetic repertoire for glycolysis was detected. In addition, genes encoding enzymes that mediate resistance against several antimicrobials and metals were identified. High resistance of C. acidurici towards bacitracin, acriflavine and azaleucine was experimentally confirmed.